2018
DOI: 10.1182/blood-2018-99-112682
|View full text |Cite
|
Sign up to set email alerts
|

Effective Lipidoid Nanoparticle Delivery In Vivo of siRNA Targeting Kappa Light Chain Production in a Murine Xenograft Model

Abstract: INTRODUCTION : Despite advances in therapy, patients with relapsed AL amyloidosis die of resistant disease. New therapies are needed. siRNA directed at the constant regions of Ig light chains (LC) reduces LC mRNA and protein from patient cells, from human myeloma and AL cell lines, and in a flank plasmacytoma model with in vivo electroporation (Blood 2014;123:3440; Gene Ther 2016;23:727). To deliver siRNA in vivo, we first tested a series of biodegradable lipidoid nanoparticles (LPN) generated through Michael … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…17 The endosome escape mechanism of biodegradable disulfide-bond-containing LNPs is not completely understood and requires further exploration. Nevertheless, we demonstrated that these new groups of lipids are versatile platforms that complex and deliver a wide range of cargo molecules, including siRNA, 14,18,19 small-molecule drugs, 20 proteins, 21,22 micro RNA (miRNA), 23 antisense oligonucleotides (ASO), 24 and mRNA. 2,4,25 Acetal-Containing pH-Responsive Lipids Recently, we further expanded the stimuli-responsive combinatorial lipids by incorporating an acid-degradable acetal group into the lipid tail.…”
Section: Disulfide-containing Reduction-responsive Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The endosome escape mechanism of biodegradable disulfide-bond-containing LNPs is not completely understood and requires further exploration. Nevertheless, we demonstrated that these new groups of lipids are versatile platforms that complex and deliver a wide range of cargo molecules, including siRNA, 14,18,19 small-molecule drugs, 20 proteins, 21,22 micro RNA (miRNA), 23 antisense oligonucleotides (ASO), 24 and mRNA. 2,4,25 Acetal-Containing pH-Responsive Lipids Recently, we further expanded the stimuli-responsive combinatorial lipids by incorporating an acid-degradable acetal group into the lipid tail.…”
Section: Disulfide-containing Reduction-responsive Lipidsmentioning
confidence: 99%
“…The endosome escape mechanism of biodegradable disulfide-bond-containing LNPs is not completely understood and requires further exploration. Nevertheless, we demonstrated that these new groups of lipids are versatile platforms that complex and deliver a wide range of cargo molecules, including siRNA, ,, small-molecule drugs, proteins, , micro RNA (miRNA), antisense oligonucleotides (ASO), and mRNA. ,, …”
Section: Synthesizing Combinatorial Biodegradable Lipid Librariesmentioning
confidence: 99%
“…These LNPs were applied to an NOD scid gamma (NSG) JJN3 intraperitoneal mouse model. 8B-3 LNPs encapsulated with siRNA targeting the IGKC gene significantly reduced circulating Kappa light chains in the NSG JJN3 mice after three daily IP injections 32 , 33 .…”
Section: Lnps For the Delivery Of Nucleic Acidsmentioning
confidence: 95%